Model TGT Berbantuan Media Snake and Ladder Untuk Meningkatkan Hasil Belajar IPAS Kelas VI SD Negeri Sarirejo 04 - Hasna Dyah Ekaputri; Siti Masfuah; Diana Ermawati (PGSD Universitas Muria Kudus, 2026)
Students' learning outcomes are low due to teaching methods that lack variety and teachers having difficulty selecting interesting readings to use. The purpose of this study is to improve students' learning outcomes by applying the TGT learning model supported by Snake and Ladder media. This study uses the Classroom Action Research (CAR) method consisting of two cycles, conducted at SD Negeri Sarirejo 04, Kecamatan Pati, Kabupaten Pati. The subjects of this study are sixth-grade students, totaling 24 people. Data were obtained through observation, interviews, and documentation using observation sheets, interview guides, and test questions. Data analysis was conducted using a descriptive quantitative approach to determine the improvement in students' learning outcomes, as well as a descriptive qualitative approach to explain the learning process during the implementation of the actions. The research results showed an increase in students' learning outcomes in process skills from 51.4% in cycle I to 83.3% in cycle II, as well as an increase in conceptual understanding from 29% in cycle I to 79% in cycle II. Overall, the research conducted in two cycles indicates that the TGT learning model using the Snake and Ladder media successfully improved the learning outcomes of sixth-grade students at SD Negeri Sarirejo 04.